2021
DOI: 10.3390/ma14144051
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of a Honeycomb-like Pattern with Cellulose Acetate and Silver Nanoparticles

Abstract: This study involved the preparation and characterization of structures with a honeycomb-like pattern (HCP) formed using the phase separation method using a solution mixture of chloroform and methanol together with cellulose acetate. Fluorinated ethylene propylene modified by plasma treatment was used as a suitable substrate for the formation of the HCP structures. Further, we modified the HCP structures using silver sputtering (discontinuous Ag nanoparticles) or by adding Ag nanoparticles in PEG into the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The changes in the chemical composition of the surface were studied using the XPS method, which under normal conditions measures only to a depth of 10 nm [ 37 ]. As an alternative elemental analysis, we have applied the EDS method to acquire elemental composition data from a larger depth, since EDS analysis enables the determination up to a depth of several hundreds of nanometers [ 38 ]. Figure 4 shows the XPS spectrum of a sample deposited with an Ag layer at 20 mA for 200 s and a table with the atomic concentration of Ag for samples sputtered at a current of 20 mA at different deposition times.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in the chemical composition of the surface were studied using the XPS method, which under normal conditions measures only to a depth of 10 nm [ 37 ]. As an alternative elemental analysis, we have applied the EDS method to acquire elemental composition data from a larger depth, since EDS analysis enables the determination up to a depth of several hundreds of nanometers [ 38 ]. Figure 4 shows the XPS spectrum of a sample deposited with an Ag layer at 20 mA for 200 s and a table with the atomic concentration of Ag for samples sputtered at a current of 20 mA at different deposition times.…”
Section: Resultsmentioning
confidence: 99%
“…However, the latest new theory confirms that hexagonal structures are formed due to highly elastic wax, elevated temperature, and surface tension, transforming circular shapes into hexagonal [12][13][14]. Based on this study, honeycomb-like patterns (HCP) have been identified as unique surfaces due to thousands of interconnected and oriented pores with high mechanical strength [15,16]. Based on the pore size and porosity, three-dimensional (3D) scaffolds resembling the in vivo shape and conditions can be created.…”
Section: Introductionmentioning
confidence: 82%
“…Short exposure of a polymer to the plasma treatment creates nanometric structures while changing the polymer surface into a porous form for a longer time [47]. Based on previous research [16,25], the plasma treatment parameters for creating the suitable surface of HCP structures were selected: duration 240 s at the power of 8 W. The changes on the prepared HCP structures' surface morphology were analyzed by two different methods, AFM and SEM. Figure 1 represents the scans of the prepared samples acquired by the SEM analysis.…”
Section: Surface Morphology Analysis Using Sem and Afm Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BF method is a simple and convenient method to fabricate highly ordered honeycomb-patterned (HCP) porous films with specific surface topography and chemical distribution, first reported by Widawski et al [ 37 ]. Many researchers have reported the antibacterial and antifouling activity of HCP films by incorporating antibacterial and antibiofilm moieties such as TiO 2 [ 24 ], silver NPs [ 38 , 39 ], silicone oil [ 40 ], etc. However, the antibacterial activity of PANI-coated HCP films has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%